L’Io del sistema, non solo il sistema dell’Io? Hegel vs. Fichte - Ricci, Vittorio (Revista Eletrônica Estudos Hegelianos, 2017)
ABSTRACT: One of the most fundamental questions concerning the relationships between Hegel and Fichte consists in the notion of I or consciousness. Hegel, from the beginning of his philosophical thinking, turned his attention to Fichte’s conception of I and expressed his appreciation of the original scheme of Fichte’s Grundsatz (and for the consequent deduction/opposition I/non-I). Hegel shared with Fichte the principle that consciousness grounds science and its essential system. However, the radical difference is that, for Hegel, consciousness is intrinsically only science’s necessary ‘appearance’. On the contrary, for Fichte, consciousness not only grounds science, but also determines its structural content and possibility. For Hegel, consciousness in itself can only be the subject of Wissen (figurative-empirical theory in the phenomenological realm) and a historical form of spirit (Erinnerung in contingent happening). In order to elaborate these two perspectives of the spirit’s ‘conceived history,’ the Entäußerung in the form of the pure concept belonging to the science is necessary; that is the indispensable element missing in Fichte’s doctrine, not only in order to explain the effective truth of consciousness but also that of science itself.